The practices and Understanding of Corporate Social Responsibility in Public sector of Pakistan: A Case of PPL-Pakistan (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
The current research investigates the practices and understanding of Corporate Social Responsibility (CSR) in public sector of Pakistan. CSR is becoming very familiar in the field of business and is getting much popularity among scholars, academicians, practitioners, and communities. But, through this paper it is identified that practice and understanding of CSR in most of the developing nations including Pakistan is philanthropic and has not fully developed in accordance with international standards. Moreover, most of the companies believe that doing charitable activities is CSR. This, off course is not the CSR as it is being practiced and developed in the West. The discourse of CSR among the developing nations is still at infancy stage and has to develop in accordance with the International standards. Further, with the help of this paper CSR and its overall structure is presented in which some key theories of CSR are also presented. The purpose of presenting this is to make aware the public companies of Pakistan to think beyond the current philanthropic approach of CSR.We believe that by broadening the practice and understanding of CSR can help companies to better develop their image before the various stakeholders. Because, we believe that CSR oriented organizations are more efficient of attracting, motivating and retaining their internal stakeholders e.g. the employees and can have better image before the external stakeholders. Thus, we believe that more empirical research is needed and we encourage the future research be carried particularly in public sector because public sector plays vital role in solving the most of the societal problems.  In this paper the extent literature on CSR is presented in which the broader perspective of CSR is discussed.